Zero Morpheme - Azita Abbasi (̒Ilm-i Zabān, 2014)
In the conjugation of root morpheme, zero morpheme is a morpheme which has semantic load but no visual representation, not in written nor spoken form. As an example, the word رفت in Persian is a third-person, simple past, singular but there are no visual representations in this word to indicate person and number. A group of linguistics analyze this verb as [رفت-Ø]verb and relate the person and number indicators to the zero morpheme. But the zero morpheme, from the viewpoint of many researchers such as Aronov (1976, 1983), Lieber (1981), Bauer (1983, 1988), Schtechaur (1992) and Melchuk (1996), has been criticized for many reasons including multiplicity of grammatical categories and meanings. In the present paper, the nature of the zero morpheme will undergo detailed analysis, and the examples of this morpheme as well as the conditions for its existence determined by linguists will be explained. Then, after providing the reasons for accepting or rejecting the zero morpheme, it will be determined, by proposing linguistic evidence, that what is referred to as the zero morpheme in different references is actually a contextual vacuum in the syntagmatic axis which is filled by the speaker by using the available linguistic and non-linguistic context.